Vivacity and Hume's Impression-Idea Distinction - (:unkn) unknown (My University, 2022)
Hume famously grounds his foundational distinction between impressions and ideas on “force and vivacity.” However, he acknowledges that vivacity is sometimes imprecise for distinguishing impressions from ideas, in, for example, the phenomena madness. Therefore, interpreters question how impressions and ideas are really differentiated. Interpretations of the impression-idea distinction traditionally take one of two forms—either attempts to better-defined vivacity in other terms, or arguments that already better-defined distinctions, like the Copy Principle, suffice to distinguish impressions from ideas. However, both approaches create unpalatable problems for interpreting Hume. This paper gives a phenomenological account of vivacity and suggests that we should read the opening movements of both the Treatise book I and the first Enquiry dialectically. This approach makes sense of the seeming inconsistency while avoiding unpalatable consequences of other approaches by diffusing the debate entirely. It also promises application in other areas of Hume studies.
Keywords: Copy Principle; David Hume; metaphor; vivacity